2008
DOI: 10.1002/col.20417
|View full text |Cite
|
Sign up to set email alerts
|

A computer‐assisted colour selection system based on aesthetic measure for colour harmony and fuzzy logic theory

Abstract: An aesthetic measure based approach for constructing a colour design/selection system is proposed in this article. In this model, an image data base for the relationships between the psychological preference of customers and clothing colour tones is built using the membership functions of a fuzzy set, and an aesthetic measure calculation method based on colour harmony is also proposed. In addition, a skin colour detection theory is proposed to construct a skin colour detection program to detect the skin colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 26 publications
0
49
0
2
Order By: Relevance
“…They can choose day to day life useful items or product, get news about trends; this allows them to makeover not only in terms of acquiring latest fashion but they can also boost up their life styles [10]. Another such system is a computerassisted color selection system that uses color synchronization and fuzzy logic to make suggestions about clothing matching with the users' skin tone [15]. Furthermore, there is a multiagent recommender system for e-tourism (MARST) [16] for recommending tourism services to the users.…”
Section: Related Workmentioning
confidence: 99%
“…They can choose day to day life useful items or product, get news about trends; this allows them to makeover not only in terms of acquiring latest fashion but they can also boost up their life styles [10]. Another such system is a computerassisted color selection system that uses color synchronization and fuzzy logic to make suggestions about clothing matching with the users' skin tone [15]. Furthermore, there is a multiagent recommender system for e-tourism (MARST) [16] for recommending tourism services to the users.…”
Section: Related Workmentioning
confidence: 99%
“…Kansei Engineering is the translating technology of a consumer's feeling of a product to the product's design elements . Many consumer and color design studies have found that gender and age are the major elements of a target consumer profile. Consumers tends to buy products that correspond to their gender .…”
Section: Implementation Proceduresmentioning
confidence: 99%
“…Hsiao and Chiu combine the concept of color emotion, harmony and preference to propose a recommendation system of color combinations. They used fuzzy set theory to assign the value of consumers' emotion and applied the aesthetic measure theory to evaluate the aesthetic of color combinations for building a personalized color selection system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsiao et al [3] used the skin color detection with color harmony theory and created an expert system. The system could help people input their skin color and get the right option for clothes color.…”
Section: Introductionmentioning
confidence: 99%